A Comparative Study of Sheep Breeds: Fattening Performance, Carcass Characteristics, Meat Chemical Composition and Quality Attributes - Suliman, G. M.; Al-Owaimer, A. N.; El-Waziry, A. M.; Hussein, E. O. S.; Abuelfatah, K.; Swelum, A. A. (Frontiers in Veterinary Science, 2021)
Carcass characteristics, chemical composition, and meat quality were evaluated in three sheep breeds: Awassi, Harri, and Najdi. Forty-five lambs of similar weight and age were raised for 90 days under similar conditions. The Harri and Najdi breeds had higher dressing-out percentages than Awassi sheep. The Awassi and Harri breeds had thicker backfat than the Najdi breed. No significant difference was found in moisture, protein, and intramuscular fat among the breeds. However, the Harri breed had a higher ash content than the Awassi and Najdi breeds. The Najdi breed had higher ultimate pH and lower cooking loss than the Awassi and Harri breeds. Awassi and Harri sheep had a higher myofibril fragmentation index, longer sarcomere length, and lower hardness and chewiness than Najdi sheep. Subjectively, no significant differences were detected between the breeds, except for flavor intensity while the Awassi sheep were rated in between and not significantly different. In conclusion, breed affected carcass characteristics, meat composition, and the quality of sheep. The dressing yield was higher in Harri and Najdi than Awassi sheep. Awassi sheep showed superior meat quality characteristics followed by Harri sheep. However, Najdi sheep had the best cooking loss percentage and flavor intensity score.